Comparative analysis of consistency of adaptations to interval interventions individualized using sport-specific techniques in well-trained soccer players - Hongjun Zhang; Sheng Li; Bingyuan Yang (Scientific Reports)
Abstract This study aimed to investigate the uniformity of adaptive changes in cardiorespiratory fitness and anaerobic power to high-intensity interval interventions (HIIT) designed using techniques specified for soccer players. Thirty well-trained athletes (age = 25 ± 3.1 years; body mass = 82.4 ± 3.4 kg; height = 183 ± 2.1 cm) were randomly assigned to two experimental groups engaging in interval intervention individualized using 30–15 Intermittent Fitness Test [HIITvIFT (two sets of 5–8 min intervals, comprising 15 s of running at 95% of VIFT followed by 15 s of passive recovery)], and small-sided game with matched timing (SSG [4 sets of 2.5–4 min 3 v 3 efforts]), as well as an active control group. Before and after a 6-week intervention consisting of three sessions per week, participants underwent a lab-based cardiorespiratory fitness test using breath-by-breath gas analyzer and non-invasive impedance cardiography to evaluate aerobic fitness and cardiac function measures. Also, anaerobic power was measured using lower-body Wingate test. Both interventions resulted in significant enhancement in all measures of cardiorespiratory fitness and anaerobic power over the training period. Analyzing inter-individual variability through determining residuals in individual changes indicated HIITvIFT results in residuals in individual changes in ventilatory threshold (VT [first (VT1) and second (VT2)]), and peak and average power output than SSG (p = 0.02, 0.04, 0.02, and 0.01, respectively). In addition, the change in maximum oxygen uptake, maximal ventilation, and average power output following HIITvIFT was notably greater than SSG (p = 0.002, 0.006, and, 0.019, respectively). There was no significant difference between HIITvIFT and SSG in cardiac hemodynamics (cardiac output and stroke volume). Overall, by facilitating more homogenous stress, HIITvIFT results in more identical physiological demands and more uniform adaptations in ventilatory threshold and anaerobic power than SSG.